Perlindungan Hukum Kreditur Terhadap Pembatalan Perjanjian Perdamaian - Irpan Hadi (Jurnal Penelitian Hukum Legalitas, 2023)
This research aims to examine and understand the implementation of peace agreement dispute resolution in the Bankruptcy Process for Delaying Debt Payment Obligations (PKPU), as well as evaluate homologation decisions against creditors based on Law No. 37 of 2004 concerning Bankruptcy and Delaying Debt Payment Obligations. The research method used in this research is normative legal research conducted as an effort to obtain the necessary data related to the problem. The results of this study reveal that legal protection for creditors, especially unsecured creditors (concurrent), is very limited due to large debts by debtors. Debtors have significant control over the postponement of debt payment obligations (PKPU) application, and secured creditors often have no influence on this decision. Asset sales after bankruptcy are often insufficient to satisfy debts, to the detriment of creditors. Therefore, government intervention is required to provide better legal protection to creditors, especially unsecured (concurrent) creditors, which takes into account their human rights and business continuity. In this context, legal measures such as action paulina and the principle of parity creditorium in the Bankruptcy Law are essential to protect creditors. Thus, this research highlights the need for improved legal protection for creditors, especially unsecured creditors, in insolvency situations in Indonesia.